The Ross procedure for everyone (Swiss Medical Weekly, 2012)
Aortic valve replacement using a pulmonary homograft is a complex procedure which provides very good functional results in most patients. Negligible valve-related morbidity, freedom from anticoagulation, and the ability to accommodate growth make it a valid therapeutic modality in infants and children. Due to the excellent quality of life which it provides, the procedure is increasingly being performed in adults. However, it has become apparent that pulmonary homograft insufficiency may be a relatively common problem. Dilatation of the pulmonary autograft is the most common complication after a Ross procedure affecting nearly one-third of patients. It was suggested that dilatation of the pulmonary autograft occurs because of a geometric mismatch between the aortic and pulmonary roots. Despite there been no morphological or physiological data, the authors believed that spatial geometry may influence the dilatation of the neo-aortic root. Herein, I analyse the actual literature stressing long-term results and predictive factors for neo-aorta failure following the Ross procedure. According to my previous morphological investigations I made a proposition of how the Ross procedure may be modified in order to include it for everyone as an aortic valve substitute.